2018
DOI: 10.1108/jfp-05-2017-0014
|View full text |Cite
|
Sign up to set email alerts
|

The impact of masculinity upon men with psychosis who reside in secure forensic settings

Abstract: STRUCTURED ABSTRACT PurposeMasculinity is a core cognitive structure that plays a central role in organising attitudinal and behavioural processes. Yet there is limited research focusing upon the meaning of masculinity for men who have a past history of violent behaviour, experience psychotic phenomena and reside in secure forensic settings.Design/methodology/approach Q methodology was used to elucidate the factors regarding how men who experience psychotic phenomena perceive their masculinity. Ten participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…Compassion involves the forgiveness to oneself in the face of adversity and accepting the shortfalls that are associated with being human (Neff, 2003). However, compassion could appear to be in conflict with traditional masculine norms such as aggression, violence and not showing vulnerability (Searle et al , 2018). Indeed, research by Reilly et al (2014) found that higher levels of self-compassion were associated with lower levels of masculine norm obedience, and traditional masculinity among military veterans was associated with lower levels of mindfulness, self-compassion and mental health-related quality of life as well as with greater levels of avoidant styles of coping (Ramon et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Compassion involves the forgiveness to oneself in the face of adversity and accepting the shortfalls that are associated with being human (Neff, 2003). However, compassion could appear to be in conflict with traditional masculine norms such as aggression, violence and not showing vulnerability (Searle et al , 2018). Indeed, research by Reilly et al (2014) found that higher levels of self-compassion were associated with lower levels of masculine norm obedience, and traditional masculinity among military veterans was associated with lower levels of mindfulness, self-compassion and mental health-related quality of life as well as with greater levels of avoidant styles of coping (Ramon et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research identified that violent men strive for power and dominance over others ( 40 , 41 ). On the contrary, Searle et al ( 33 ) identified a predominantly pro-social development framework for the representation of masculinity in forensic male patients with a psychotic illness.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Bengtsson‐Tops et al (2014) found that people living in supportive housing who reported feeling that nothing ever happened in their daily lives only became more passive. Stefan and Tomas behaviour can therefore be understood as frustration with the living conditions more than expressing masculinity (Searle et al, 2018).…”
Section: Discussionmentioning
confidence: 99%